2017
DOI: 10.1002/app.44888
|View full text |Cite
|
Sign up to set email alerts
|

Surface molecularly imprinted polymer microspheres based on nano‐TiO2 for selective recognition of kaempferol

Abstract: The molecular imprinting technique is a new method for preparing molecularly imprinted polymers (MIPs) with specific molecular recognition sites for certain target molecules. In this study, a novel, facile preparation method was presented, called "seed precipitation polymerization," for the synthesis of MIPs via surface imprinting and a support matrix. In the polymerization process, kaempferol was used as the template molecule, methacrylic acid as the functional monomer, nano-TiO 2 as the support, azodiisobuty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Huang et al [64] used nano-TiO 2 as the support matrix, 4-VP as the functional monomer, kaempferol as the template molecule, ethylene glycol dimethacrylate (EDMA) as the cross-linking agent to prepare kaempferol imprinted polymers and nano-TiO 2 -based MIPs were obtained at last after removing the template. The polymer particles made in this work appear as uniform microspheres with high selectivity and template recognition.…”
Section: General Methods For the Preparation Of Mips Modified Tio2 mentioning
confidence: 99%
“…Huang et al [64] used nano-TiO 2 as the support matrix, 4-VP as the functional monomer, kaempferol as the template molecule, ethylene glycol dimethacrylate (EDMA) as the cross-linking agent to prepare kaempferol imprinted polymers and nano-TiO 2 -based MIPs were obtained at last after removing the template. The polymer particles made in this work appear as uniform microspheres with high selectivity and template recognition.…”
Section: General Methods For the Preparation Of Mips Modified Tio2 mentioning
confidence: 99%
“…In recent years, several studies have reported the preparation of KA‐MIPs 20–22 . Methacrylic acid, acrylamide and 4‐vinylpyridine were usually used as the functional monomer.…”
Section: Introductionmentioning
confidence: 99%
“…12,19 In recent years, several studies have reported the preparation of KA-MIPs. [20][21][22] Methacrylic acid, acrylamide and 4-vinylpyridine were usually used as the functional monomer. Ethylene glycol dimethacrylate (EDMA) was widely used as the crosslinker.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the downsides of mass polymerization, increasingly modern and complex polymerization strategies have been proposed to acquire MIPs with various structures, such as dots, solid structures, and coatings. At first, globules are commonly used for pressing segments for chromatography or solidphase extraction (SPE) [4] and are normally integrated by suspension polymerization [5], seed polymerization [6], emulsion polymerization [7], and precipitation polymerization [8]. Solid packing polymers are used for in situ segments that are prepared to be used directly after the evacuation of the format [9][10].…”
Section: ■ Introductionmentioning
confidence: 99%